A review of carbon dynamics and assessment methods in the miombo woodlands. Issue 2 (3rd April 2017) - Handavu, Ferdinand; Chirwa, Paxie W; Syampungani, Stephen; Mahamane, Larwanou
Abstract : Provision of accurate carbon (C) measurements and analysis are critical components in quantification of C stocks. The objectives of this review were to (1) compile and synthesise current knowledge of available methods for C stock estimation, (2) examine socio-economic drivers of land-use and land-cover change and their influence on woodland C stocks and (3) identify gaps of knowledge and methodological inadequacies in understanding factors affecting C stocks of major C pools for miombo woodlands of southern Africa. The review shows that quantification of forest C is a challenging task, mainly associated with knowledge gaps and methodological challenges. This has brought about a high level of uncertainty and inconsistencies, mainly due to the accounting methods applied. Furthermore, it is necessary to consider the inherent spatial heterogeneity of the landscape and stand density in order to ensure development of accurate C estimation methodologies when developing C models. Ultimately, developing widely applicable biomass models for southern Africa will require detailed assessments, including different aspects of wood C fractions. It is evident from the review that a comprehensive understanding of socio-economic drivers of land-use and land-cover change is necessary to ensure better-informed sustainable forest management policy direction, strategy and practice to deliver C and livelihood options.